1998
DOI: 10.2307/1369898
|View full text |Cite
|
Sign up to set email alerts
|

Wood Thrush Postfledging Movements and Habitat Use in Northern Virginia

Abstract: We monitored 42 radio-tagged, fledgling Wood Thrushes (Hylocichla mustelina) to investigate movement and habitat use during the postfledging period. Fledglings' mean (? SE) age at dispersal from the natal sites was 32.5 5 0.6 days post hatching. First dispersal sites were located 1.5 ? 0.3 km from the natal site. All young joined flocks of juveniles, except three birds that remained solitary. Sixteen birds stayed at the first dispersal site until departure on migration, whereas nine visited additional dispersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…These findings are consistent with previous studies that reported higher Wood Thrush densities in 100-m buffer zones surrounding regeneration cuts, and in unharvested stands that were adjacent to recently harvested stands (Wallendorf et al 2007, Kendrick et al 2015. The Wood Thrush is typically classified as a mature forest species, but juveniles and adults make use of shrubland habitat and small canopy openings during the post-breeding period (Anders et al 1998, Rappole et al 1998, Porneluzi et al 2014). Thus, the increased diversity in forest age structure in evenaged compartments may have promoted Wood Thrush populations in the unharvested and/or thinned stands of the compartment, even as abundance declined inside the actual clearcut openings (Vitz and Rodewald 2006).…”
Section: Spatial and Temporal Variation In Management Effectssupporting
confidence: 91%
“…These findings are consistent with previous studies that reported higher Wood Thrush densities in 100-m buffer zones surrounding regeneration cuts, and in unharvested stands that were adjacent to recently harvested stands (Wallendorf et al 2007, Kendrick et al 2015. The Wood Thrush is typically classified as a mature forest species, but juveniles and adults make use of shrubland habitat and small canopy openings during the post-breeding period (Anders et al 1998, Rappole et al 1998, Porneluzi et al 2014). Thus, the increased diversity in forest age structure in evenaged compartments may have promoted Wood Thrush populations in the unharvested and/or thinned stands of the compartment, even as abundance declined inside the actual clearcut openings (Vitz and Rodewald 2006).…”
Section: Spatial and Temporal Variation In Management Effectssupporting
confidence: 91%
“…compared with non-dispersers [17,44]. In migratory species, young can acquire knowledge about the natal area by remaining near their birth site before the onset of migration [45,46]. Natal dispersers may therefore lack such knowledge about their settlement area.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported similar behaviour, with both adult and juvenile Wood Thrushes (Hylocichla mustelina (J.F. Gmelin, 1789)) feeding, from the time of dispersal from the nest site until fall migration, on a variety of fruits that successively reach maturity during that period (Anders et al 1998;Vega Rivera et al 1998a, 1998b, 1999. Major (2010) observed an increased in fruit trees and shrub abundance <10 years after PCT, similar to what we observed (PCT-96 vs. PCT-86).…”
Section: Size Composition and Use Of Home Rangesmentioning
confidence: 91%